Students' Barriers in Learning English Through Online Learning - Ifna Nifriza; Desfi Yenti (Linguistic, English Education and Art (LEEA) Journal, 2021)
This study aims to identify student barriers in learning English through online learning in class X SMKN 3 Payakumbuh. This research method is descriptive qualitative. Participants were selected using purposive sampling. The questionnaire used as a data source consists of 32 items. The results showed that the barriers faced by students included understanding language, language anxiety, adaptation struggle, diverting attention to the other side, technical issues, cost of online education implementation, technological competence and computer literacy. In conclusion, there are 8 barriers faced by students in learning English through online learning. Understanding language is the most common barriers faced by students, while the least barriers faced by students is computer literacy. Keywords: Online Learning, Student Barriers